2010
DOI: 10.1089/tmj.2009.0136
|View full text |Cite
|
Sign up to set email alerts
|

Goal Setting Using Telemedicine in Rural Underserved Older Adults with Diabetes: Experiences from the Informatics for Diabetes Education and Telemedicine Project

Abstract: Televisits can be successfully used to collaboratively establish behavior change goals to help improve diabetes self-management in underserved elderly rural adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 19 publications
3
72
0
12
Order By: Relevance
“…ICTs are currently being used in developed [3] and developing countries [4][5][6] and have been used to improve access to sources of knowledge for both patients and health care providers. However, the undersized health and ICT sector in a country such as Afghanistan limits its potential and wider benefits [7].…”
Section: Introductionmentioning
confidence: 99%
“…ICTs are currently being used in developed [3] and developing countries [4][5][6] and have been used to improve access to sources of knowledge for both patients and health care providers. However, the undersized health and ICT sector in a country such as Afghanistan limits its potential and wider benefits [7].…”
Section: Introductionmentioning
confidence: 99%
“…5 Several studies using telehealth in rural areas have reported improved knowledge of diabetes, self-efficacy, dietary adherence, glucose monitoring, and glycemic control. [18][19][20][21] A large body of evidence supports a short-term effect of diabetes self-management education. [22][23][24][25] In a systematic review of randomized controlled trials, Norris et al 26 reported that, in general, the effectiveness of diabetes interventions was short-lived; improvements in glycemic control, knowledge of diabetes, and diet were observed in the short term, with no significant differences observed between the intervention versus control group long term ( >6 months postintervention).…”
mentioning
confidence: 99%
“…Otera-Sabogal et al (2010) demonstrate that a proactive, educational approach statistically improved blood glucose levels, LDL cholesterol, and increased self-care management of type II diabetes. West et al (2010) findings suggest that 68% of behavioural goals were met or improved in patients with diabetes. A systematic review, which included 21 studies (after eliminating 6,325 studies based on quality measures) suggested that patients receiving remote monitoring experienced significantly lower hospital readmission, mortality rates, and emergency department visits (Polisena et al, 2010).…”
Section: Quality and Millmentioning
confidence: 87%